Fast Start-Up Microfluidic Microbial Fuel Cells With Serpentine Microchannel - Luo, Xian; Xie, Wenyue; Wang, Ruijie; Wu, Xiaoshuai; Yu, Ling; Qiao, Yan (Frontiers in Microbiology, 2018)
Microfluidic microbial fuel cells (MMFCs) are promising green power sources for future ultra-small electronic devices. The MMFCs with co-laminar microfluidic structure are superior to other MMFCs according to their low internal resistance and relative high power density. However, the area for interfacial electron transfer between the bacteria and the anode is quite limited in the typical Y-shaped device, which apparently restricts the current generation performance. In this study, we developed a membraneless MMFC with serpentine microchannel to enhance the interfacial electron transfer and promote the power generation of the device. Owing to the merit of laminar flow, the proposed MMFC was working well without any proton exchange membrane. At the same time, the serpentine microchannel greatly increased the power density. The S-MMFC catalyzed by Shewanella putrefaciens CN32 achieves a peak power density of 360 mW/m2 with the optimal channel configuration and the flow rate of 5 ml/h. Meanwhile, this device possesses much shorter start-up time and much longer duration time at high current plateau than the previous reported MMFCs. The presented MMFC appears promising for biochip technology and extends the scope of microfluidic energy.